The Relationship Between The Level of Reproductive Health Knowledge and The Prevention Behavior of Sexually Transmitted Infections Among Adolescents in State Senior High School 12, Bekasi City, West Bekasi District, Bekasi City in 2025 - lis Sri Hardiati; Eriane Jahtun Titania (Jurnal Ners, 2026)
Background: Adolescents are a strategic age group in the national development process, yet they are also among the most vulnerable to various reproductive health issues. Adolescence is characterized by rapid biological, psychological, and social changes, often unmatched by an adequate understanding of reproductive responsibilities. This significant proportion demands serious attention to improving the quality of adolescent health, particularly in reproductive health. A lack of accurate and reliable information has the potential to encourage risky sexual behavior, including premarital relations, which ultimately increases the likelihood of sexually transmitted infections (STIs). Adolescents with high self-confidence and open communication with their parents are generally better able to make healthy decisions regarding sexual activity. However, the cultural taboo surrounding discussing sexuality in Indonesia often hinders such communication. This study aims to provide insight into the influence of psychosocial factors on preventive behavior among students at SMA Negeri 12 Bekasi.Research Objective: To determine the relationship between knowledge levels about reproductive health and STI prevention behavior among adolescents at SMA Negeri 12 Bekasi.Research Method: This study uses a descriptive analytical approach with a cross-sectional method using the Chi-square test. The study sample consisted of 80 students from SMAN 12 Bekasi City, selected using random sampling.Results: The study showed a significant relationship between reproductive health knowledge and sexually transmitted infection prevention behavior among adolescents at SMAN 12 Bekasi City in 2025.Conclusions and Recommendations: There is a significant relationship between reproductive health knowledge and sexually transmitted infection prevention behavior among adolescents at SMAN 12 Bekasi City in 2025. Health institutions can improve adolescents' understanding of sexuality through seminars or outreach programs organized by schools in collaboration with local community health centers. Furthermore, parents need to be involved in this process by attending seminars and communicating openly with their children. Furthermore, health services should be easily accessible to adolescents at schools and local community health centers..